PS-C08-11: RELATIONSHIP OF AMBULATORY WAKE SYSTOLIC BLOOD PRESSURE AND COGNITIVE FUNCTIONING IN CHILDREN AND ADOLESCENTS: THE SHIP-AHOY STUDY. (January 2023) - Hooper, Stephen; Lande, Marc; Flynn, Joseph; Samuels, Joshua; Meyers, Kevin; Ferguson, Michael; Urbina, Elaine
Abstract : Objective: 24-Hour Ambulatory blood pressure monitoring (ABPM) has been shown to be associated with cognitive functioning in both adults and children with hypertension. Few studies have examined this relationship in youth with normal to mildly elevated blood pressure (BP). We aimed to address this gap in the literature by examining the relationship between average wake systolic BP and targeted cognitive abilities in children and adolescents with normal to mildly elevated BP. Design: Cross-sectional cohort study across six academic centers in the United States. Methods: Participants were part of the SHIP AHOY Project examining target organ damage in children and adolescents with normal to mildly elevated BP. Patients were recruited from pediatric nephrology and/or cardiology clinics and had BP levels > 75th percentile to > 95th percentile). Ascertainment was designed to balance BMI across this BP range by actively recruiting normotensive subjects with obesity. Exclusion criteria included stage 2 hypertension, use of antihypertensive or lipid-lowering medication in the past 6 months, diabetes mellitus (type 1 or 2), kidney disease, or other chronic medical conditions. The primary exposure for this study was average wake Systolic BP. Cognitive variables included the Test of Nonverbal Intelligence, Woodcock-Johnson-V Verbal Attention, and Conners Continuous Performance Test-3 Errors of Omission and Errors of Commission. Preliminary analyses comprised the use of unadjusted linear regressions for the entire sample, with follow-up analyses planned to include key covariates for any significant findings. Results: We recruited 397 adolescents, ages 11–19 years (M∼15.5 yrs.), who comprised approximately 60% males and 53% white. About 25% of the participants had caregivers with a high school degree or less. About 40% of the sample had elevated BP (> 90th percentile). There was a significant relationship between wake average systolic BP and Verbal Attention (p < .009); and wake average systolic BP and Errors of Commission (p < .026). All findings were in the expected direction with higher average wake BP being related to lower performance on the attention-related variables. SBP and Errors of Omission approached significance (p < .07), while Nonverbal IQ was nonsignificant (p < .34). Conclusions: Higher average wake BP, even in adolescents with BP below the hypertensive range, is associated with lower performance on tests of attention regulation and response inhibition. These findings suggest that efforts to minimize associated neurocognitive dysfunction in the late adolescence and young adult years should begin before the presence of hypertension.